Choosing e-commerce strategies : a case study of eBay.vn partnership - Le-Nguyen, Khuong; Guo, Yue, active 2016 (London : Palgrave MacMillan UK, 2016)
The case uses the story of one of the leading e-commerce firms in Vietnam to introduce students to concepts and models of e-commerce, and in particular, to help students get familiar with cultural, ethical and legal issues in doing cross-border e-commerce. After solving the top three challenges in doing e-commerce in Vietnam within the past 9 years - enabling a reliable and secured online transaction, building customers' trust in buyers and providing an effective shipping service, the CEO needed to consider whether he should expand his proven successful domestic ecosystem extensively or build a completely new one to serve his company's strategic move: doing cross border e-commerce in Southeast Asia where there exist established players in the highly competitive and technology savvy market. Such a key strategic event occurred in early 2014.
Originally Published InLe-Nguyen, K., & Guo, Y. (2016). Choosing e-commerce strategies: A case study of eBay.vn partnership. Journal of Information Technology Teaching Cases, 6, 1-14.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Weshop -- Management; Electronic commerce -- Management -- Vietnam -- Case studies; Electronic commerce -- Social aspects -- Case studies; Electronic commerce -- Moral and ethical aspects -- Case studies; Electronic commerce -- Law and legislation -- Case studies